ChemInform Abstract: Vibsatins A and B, Two New Tetranorvibsane‐Type Diterpenoids from Viburnum tinus cv. variegatus. Issue 29 (22nd July 2014) - Gao, Xiu; Shao, Li‐Dong; Dong, Liao‐Bin; Cheng, Xiao; Wu, Xing‐De; Liu, Fei; Jiang, Wei‐Wei; Peng, Li‐Yan; He, Juan; Zhao, Qin‐Shi
Abstract Vibsatins A, (I), and B, (II), are the first examples of 14, 15, 16, 17‐tetranorvibsane diterpenoids containing a core bicyclo[4.2.1]nonane moiety, which represents a new subtype of vibsane‐type diterpenoids.